1998
DOI: 10.1090/s0002-9939-98-04450-5
|View full text |Cite
|
Sign up to set email alerts
|

Zeros of the Zak transform on locally compact abelian groups

Abstract: Let G be a locally compact abelian group. The notion of Zak transform on L 2 (R d) extends to L 2 (G). Suppose that G is compactly generated and its connected component of the identity is non-compact. Generalizing a classical result for L 2 (R), we then prove that if f ∈ L 2 (G) is such that its Zak transform Zf is continuous on G × G, then Zf has a zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…A Borel section of Γ/Λ is a set of representatives of this quotient that is a Borel set. It can be proved that there always exists a relatively compact Borel section P ⊆ Γ, which we will call a fundamental domain; see [4,16]. As Λ is countable and the Haar measure of Γ, denoted m, is Borel regular, we always have 0 < m(P ) < ∞.…”
Section: Extension To Lca Groupsmentioning
confidence: 99%
“…A Borel section of Γ/Λ is a set of representatives of this quotient that is a Borel set. It can be proved that there always exists a relatively compact Borel section P ⊆ Γ, which we will call a fundamental domain; see [4,16]. As Λ is countable and the Haar measure of Γ, denoted m, is Borel regular, we always have 0 < m(P ) < ∞.…”
Section: Extension To Lca Groupsmentioning
confidence: 99%
“…Also in [15], it was seen that L 2 (G/L) ∼ = L 2 (S L ), when G is a second countable and LCA group and L is a uniform lattice in G.…”
Section: Introductionmentioning
confidence: 99%
“…For a uniform lattice L in G, a fundamental domain is a measurable set S L in G, such that every x ∈ G can be uniquely written as x = ks, for k ∈ L and s ∈ S L . The existence of a relatively compact fundamental domain for a uniform lattice in an LCA group G is guaranteed by [15,Lemma 2], and it has been shown that S L has positive measure (see [14], [15]). For a uniform lattice L, a closed subspace V ⊆ L 2 (G) is called L-invariant if it is invariant under translations by elements of L. In other…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the integers Z, finite cyclic groups Z/nZ and the circle group T are important when sampling or periodizing Gabor frames on R [26,29,30,39]. Other considerations on general locally compact abelian groups include [21,26,32], and Balian-Low type phenomena were proved to hold for finite groups in [33].…”
Section: Introductionmentioning
confidence: 99%